ANALYSIS PROGRAM COMPLEXES OF AUTOMATED ENGINEERING OF AUTOMOBILE ROADS - , Н. О., О. В. (Municipal economy of cities. Series: «Economy science», 2018)
The systems of computer-aided engineering are discussed in this article, which are used in the practice of engineering automobile roads. Computer-aided designs allow to process а large information in the different areas of the road engineering (engineer-geodesic, engineer-geological etc.), to form informative spaces, where initial design data of district and future highway project decisions are reflected. The main shortcomings and advantages of modern CAD software products of automobile roads were identified as a result of the analysis of their capabilities. Keywords: computer-aided engineering systems, automobile roads engineering, automated engineering of automobile road, automated engineering of longitudinal cross section.